Net-ativismo e mobilizações sociais no consumo de serviços de saúde - Hilario, Renata Soares (2019)
21 years ago Gilberto Gil made history with the song “Pela Internet” (“Via the Internet, in a free translation) as the first song ever to be live-streamed online, across the globe, and announced “I want to be on the net, to promote a debate”. Web activism is an expression of the political exercise from users of the cybernetic world, especially social media. The expansion of social media use by consumers brought significant changes on the company, service and client relationship due to the fact that its relevance became a focal point on the management of online manifestations, since consumers have now realized the power of this channel and the possibility of being heard when they can’t have their rights guaranteed, keeping in mind that such statements are not exclusively related to consumers’ discontent, but also to the collective well-being matters and their consequences in society, concept we define as net-ativism (web activism, in a free translation) and which will be deepened throughout the study. The purpose of this research is to comprehend digital activism in terms of the consumption of health services, under the assumption that this segment is not yet effectively prepared to manage crisis situations on social media with its own consumers, and due to the peculiarity of the section responsible for dealing with the human being’s most precious possession: health. Seeking to understand digital activism in terms of the consumption of health services, this thesis has as its study object a movement organized by the civil society, called Movimento Chega de Descaso (No More Neglect Movement, in a free translation), which carries in its narrative the battle against the carelessness in both public and private health systems in Brazil, taking social media as the column to manifest different complaints. In order to reach the main goal, which is to comprehend digital activism in terms of the consumption of health services, as much as specific goals, we continue with the MCD case doing interviews with one of the movement’s founders, professionals somehow connected to the theme, such as digital communication specialists, ombudsman, regulatory body and social media specialist academics, and also a documental analysis of posts made on the movement’s fanpage. The results were rated with qualitative research tools, through recorded interviews that brought forth a mini documentary about the subject. For such, a tooling for analysis of content to the creation of categories and comments through thematic blocks was used. As for contributions, this study supports consumers to widen their view and knowledge over the dynamic of health insurances on emergency cases which require knowing of contractual policies, as well as supporting professionals working with communication, marketing and management to make assertive decisions when dealing with a crisis of institutional image. In addition to it, there are few studies in Brazil reporting the experience of health insurance consumers and their relationship with social media, which will also contribute in terms of management scopes.